A RANDOMIZED, PLACEBO-CONTROLLED STUDY OF INTRAVITREAL OCRIPLASMIN IN PEDIATRIC PATIENTS SCHEDULED FOR VITRECTOMY. Issue 3 (March 2016) - Drenser, Kimberly; Girach, Aniz; Capone, Antonio
Abstract : Purpose: To evaluate safety and preliminary efficacy of 175 μ g of intravitreal ocriplasmin in pediatric patients scheduled for vitrectomy. Methods: Based on a single-center, prospective, randomized, placebo-controlled, and double-masked Phase 2 study, 22 pediatric patients scheduled for vitrectomy were randomized 2:1 to 175- μ g ocriplasmin injection or placebo. Treatment was administered midvitreous 30 minutes to 60 minutes before vitrectomy. Safety was assessed by reported adverse events (AEs), ophthalmologic examinations, fundus photography, and fluorescein angiography. The primary efficacy endpoint was the proportion of eyes with total macular posterior vitreous detachment before vitrectomy or after application of suction. Secondary endpoints included vitreous liquefaction assessment before vitrectomy and immediate postoperative retinal reattachment. Results: All patients experienced at least 1 AE. Most AEs were ocular and occurred in the study eye. Serious AEs were reported for 2 of 16 eyes (3.4%) in the ocriplasmin group and 2 of 8 eyes (11.1%) in the placebo group. One case of lens subluxation due to zonular disruption was observed in the ocriplasmin group. A clear efficacy signal was not observed. Conclusion: Intravitreal injection of 175 μ g of ocriplasmin was tolerated in pediatric patients before vitrectomy; however, the small sample size in this study precluded adequate efficacy comparisons. AEs reported were consistent with those anticipated in pediatric patients. Abstract : In pediatric patients scheduled for vitrectomy, safety assessment showed that ocriplasmin did not demonstrate a higher risk for adverse events compared with placebo. Adverse events were as anticipated in pediatric intravitreal injections. The small sample size precluded definitive efficacy comparisons.